A New Reference Axis for Tibial Component Rotation in Total Knee Arthroplasty: A Three-dimensional Computed Tomography Analysis - Jin, Yan; Li, Pingyue; Yang, Yiming; Zeng, Xianli; Shen, Hongyuan; Zhang, Lihang; Tsai, Tsung-Yuan; Chen, Jiarong (Frontiers in Surgery, 2022)
The purpose of this study was to introduce a new reference axis for tibial rotation in total knee arthroplasty (TKA) and verify its reliability. A consecutive series of 80 knees that underwent TKA from 2018 to 2020 as well as 80 healthy knees were analyzed using a three-dimensional tibial model. A coordinate system was established based on the standard TKA tibial cut. The line connecting the lateral-tibial eminence and the medial 1/3rd of the tibial tubercle or the medial border of the tibial tubercle was identified as the lateral eminence line (LE line) and the medial lateral eminence line (MLE line), respectively. To evaluate the reliability of the new reference axis, Akagi's line, the medial third of the tibial tubercle (1/3 line) was compared with the LE and MLE lines by measuring the angle between the lines and the Z-axis. In the coronal view, the intersection angle (TPA), which is composed of the line connecting the center of the medial and lateral tibial plateau with the Z-axis, was measured. The mean angle between Akagi's line and the Z-axis in the healthy group and the osteoarthritis (OA) group was 87.57 ± 3.48° and 87.61 ± 3.47°, respectively. The mean angle between the LE line and Z-axis in the healthy and OA groups was 87.15 ± 4.13° and 86.78 ± 3.95°, respectively. A weak correlation was found between the TPA and Akagi's line and the 1/3 line. A moderate correlation was observed between the TPA and LE lines. There were no significant differences between the healthy and OA groups (P > 0.05) in any of the four reference axes. The LE line showed excellent intra- and inter-observer reliability and reproducibility. The novel and easily drawn LE line is a preferable option for tibial component rotational alignment in TKA.